PENGGUNAAN APLIKASI WAYGROUND SEBAGAI PEMBELAJARAN INTERAKTIF - Akmal Syarifudin Zaidan; Hamam Burhanuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the use of the Wayground application as an interactive learning medium in supporting the learning process in the digital era. The research employs a qualitative method with a library research approach, analyzing various sources such as books, academic journals, and previous studies. The findings indicate that Wayground plays a significant role in enhancing student interactivity and learning motivation through the integration of gamification elements, real-time feedback, and ease of access. The platform can be implemented across different stages of learning, including introduction, core activities, and evaluation, and is applicable in online, offline, and blended learning models. However, the use of Wayground also presents several limitations, such as dependence on technological infrastructure, the potential for superficial learning, and varying impacts of competitive elements on students. Therefore, its implementation should be carefully integrated with appropriate instructional strategies and supported by teachers’ competencies and adequate facilities. In conclusion, Wayground has strong potential as an effective learning medium in creating more interactive, engaging, and meaningful learning experiences.